A Phase I, Randomized, Single-Dose Study to Evaluate the Biosimilarity of HOT-3010 to Adalimumab Among Healthy Chinese Male Subjects - Zhang, Hong; Chen, Hong; Li, Xiaojiao; Wu, Min; Zhu, Xiaoxue; Li, Cuiyun; Liu, Jingrui; Wei, Haijing; Hu, Yue; Wang, Jingjing; Yang, Yongmin; Zhu, Xiangyang; et al. (Frontiers in Pharmacology, 2021)
Objective: This study explored the bioequivalence of a proposed biosimilar HOT-3010 vs. its reference product (adalimumab) among healthy Chinese male subjects. The study also investigated the tolerance, immunogenicity, and pharmacokinetics (PK) of them. Methods: A randomized, double-blind, two-arm, parallel study was performed to examine the bioequivalence of HOT-3010 (40 mg) with that of adalimumab (Humira®, AbbVie) as a reference drug. The study subjects were followed up for 71 days. Results: PK properties exhibited by HOT-3010 (N = 66) and adalimumab (N = 68) groups were similar. The 90% confidence intervals of the ratios for Cmax, AUC0-t, and AUC0∞ were observed to be in the range 80–125% on comparing the two groups. For anti-drug antibodies (ADA), the number of subjects found to be positive in the HOT-3010 group and adalimumab group were 29 (43.94%) and 32 (47.06%), whereas 27 (40.91%) and 27 (39.71%) subjects were found to be positive for NAb, respectively. Treatment-related treatment-emergent adverse events (TEAEs) were recorded in 32 subjects each in both the groups, respectively. Conclusion: The PK characteristics and immunogenicity exhibited by HOT-3010 were similar to that of the reference product, adalimumab. The safety profiles were similar in both the treatment groups with mild-moderate adverse effects.